2010
DOI: 10.1128/iai.01084-09
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Serum Clearance of Botulinum Neurotoxin Achieved Using a Pool of Small Antitoxin Binding Agents

Abstract: Antitoxins for botulinum neurotoxins (BoNTs) and other toxins are needed that can be produced economically with improved safety and shelf-life properties compared to conventional therapeutics with large-animal antisera. Here we show that protection from BoNT lethality and rapid BoNT clearance through the liver can be elicited in mice by administration of a pool of epitope-tagged small protein binding agents together with a single anti-tag monoclonal antibody (MAb). The protein binding agents used in this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
56
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 27 publications
6
56
1
Order By: Relevance
“…32 and 6). We have found that VHH heteromultimer VNAs possess additional potential therapeutic advantages over conventional mAb products such as 1) the option to co-administer an anti-tag effector antibody that binds multiple tags on the VNAs (11,13) to promote antibody Fc effector functions such as serum clearance (33), 2) the ability to target multiple toxins with one biomolecule (12,16), and 3) the use of VNA gene therapy as an effective means to provide prolonged antitoxin protection (34,35). Simple addition of an albumin binding peptide (34,36) can dramatically improve the serum stability of VNAs (34).…”
Section: Discussionmentioning
confidence: 99%
“…32 and 6). We have found that VHH heteromultimer VNAs possess additional potential therapeutic advantages over conventional mAb products such as 1) the option to co-administer an anti-tag effector antibody that binds multiple tags on the VNAs (11,13) to promote antibody Fc effector functions such as serum clearance (33), 2) the ability to target multiple toxins with one biomolecule (12,16), and 3) the use of VNA gene therapy as an effective means to provide prolonged antitoxin protection (34,35). Simple addition of an albumin binding peptide (34,36) can dramatically improve the serum stability of VNAs (34).…”
Section: Discussionmentioning
confidence: 99%
“…One possibility for this enhanced efficacy was accelerated clearance of the toxin through the FcR pathway. The therapeutic benefit of rapid clearance has been shown for botulinum toxin (43,44) where mAbs binding to epitope tags decorate the toxin with multiple Fc domains, leading to accelerated FcR-mediated clearance. We confirmed that such a mechanism was activated when mAb 20B1 and mAb 14G8 were used in combination, and thus accelerated clearance of SEB from mouse serum via an FcR-mediated pathway was documented (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To promote toxin clearance, the VNA can be coadministered with a single antitag MAb, the efAb, that binds to multiple epitopic tags engineered into each VNA molecule. When VNAs are bound at separate sites on the toxin and each VNA is bound to two or more efAbs through the tags, the toxin becomes decorated by sufficient efAbs to promote liver clearance (30), presumably by low-affinity FcRs.…”
mentioning
confidence: 99%